2006
DOI: 10.1016/j.stam.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Functional intermetallic compounds in the samarium–iron system

Abstract: Magnetism of intermetallic compounds SmFe 2 , SmFe 3 , Sm 6 Fe 23 , and SmFe 7 were studied in detail using single crystals and the use of these materials has been discussed. SmFe 2 and Sm 6 Fe 23 have cubic magnetocrystalline anisotropy and the easy axis of magnetization in the [111] direction. SmFe 2 has giant negative magnetostriction that can be used for microactuator or ultrasonic generator. SmFe 3 has a relatively large saturation moment and uniaxial anisotropy, which are promising for application as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The Curie temperature of the samples increased from 130 • C to 361 • C with the boron addition to the alloy, due to the existence of SmFe 3 phase in the microstructure. The saturation magnetization has the highest value of 155.5 emu/g and decreases to its lowest value of 97.9 emu/g for the sample at x = 4 because Sm 2 Fe 17 has the higher saturation magnetization (117 emu/g) than that of SmFe 3 phase (80.7 emu/g) [5]. In the study, boron addition and heat treatment at 1000 • C resulted in an evolution of the phase constitution that caused changes in magnetic properties of the alloy instead of occupation of boron atoms in the interstitial sites of Sm 2 Fe 17 structure such as C and N.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Curie temperature of the samples increased from 130 • C to 361 • C with the boron addition to the alloy, due to the existence of SmFe 3 phase in the microstructure. The saturation magnetization has the highest value of 155.5 emu/g and decreases to its lowest value of 97.9 emu/g for the sample at x = 4 because Sm 2 Fe 17 has the higher saturation magnetization (117 emu/g) than that of SmFe 3 phase (80.7 emu/g) [5]. In the study, boron addition and heat treatment at 1000 • C resulted in an evolution of the phase constitution that caused changes in magnetic properties of the alloy instead of occupation of boron atoms in the interstitial sites of Sm 2 Fe 17 structure such as C and N.…”
Section: Resultsmentioning
confidence: 91%
“…With the addition of boron, the saturation magnetization decreased to its lowest value of 97.9 emu/g for the sample at x = 4. This may be due to the decrease in the amount of Fe in the microstructure and also due to the fact that Sm 2 Fe 17 has the higher saturation magnetization (117 emu/g) than that of SmFe 3 phase (80.7 emu/g) [5].…”
Section: Materials and Equipmentsmentioning
confidence: 99%
“…This phenomenon was investigated in our previous studies [ 21 , 22 ]. Although the amount of ɑ-Fe phase decreased and the ɑ-Fe phase disappeared as the amount of Sm increased, it was found that excessive Sm addition resulted in the formation of a Sm-rich phase, which causes a decrease in saturation magnetization [ 36 ]. Therefore, the Sm ratio that achieves the smallest amount of the ɑ-Fe phase without the formation of the SmFe 3 phase should be selected.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic materials are mostly intermetallics like Sm−Fe compounds for magnetic recording and Sm−Co compounds as permanent magnets. 1 SmCo 5 is one of the strongest permanent magnet materials, 2 which outperforms many others for high-temperature applications because of its high Curie temperature, T C , of 1015 K (compare to e.g. Nd 2 Fe 14 B with T C = 600 K).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Its compounds find widespread application as functional materials due to their magnetic, optic, or nuclear characteristics. Magnetic materials are mostly intermetallics like Sm–Fe compounds for magnetic recording and Sm–Co compounds as permanent magnets . SmCo 5 is one of the strongest permanent magnet materials, which outperforms many others for high-temperature applications because of its high Curie temperature, T C , of 1015 K (compare to e.g.…”
Section: Introductionmentioning
confidence: 99%